The effect of CR, ROE, and DER on stock return building construction sebsector companies listed on The Indonesia Stock Exchange year 2018- 2020 - Amruddin Amruddin; Arman Arman; Sri Mulyani (STIE Bangkinang Publishing, 2022)
This research aims to determine the effect of CR, ROE and DER simultaneously and partially on stock returns of Building Construction Subsector companies listed on the stock exchange in 2018-2020. The analysis used in this study is multiple linear analysis with a total sample of 12 banking companies. Hypothesis testing is done by f-test and t-test. Based on the results of the study, it can be concluded that simultaneously on stock returns CR, ROE and PER have a significant effect, while partially from the three variables tested, only one variables have an effect on stock returns, namely CR, while ROE dan DER has no effect on stock returns. listed on the Indonesia Stock Exchange for the 2018-2020 period. The close relationship between the independent variable and the dependent variable is quite strong with the contribution of the independent variable to the dependent variable of 14.1%.